Navigating Narratives: An Epistemological Exploration of Visually Impaired Graduates through the Social Model of Disability and Labov’s Analytical Framework - Hassan, Visama; Muna, Fathimath; Mcxin Tee (Jurnal Pendidikan Bitara UPSI, 2025)
The research process is vital for any research, as it helps to discover issues and reveal new information. Finalising the methodology of the study is important, as it gives the research a clear structure and ensures consistent and reliable data collection and analysis. This study presents the methodological framework employed to explore the perceptions and experiences of visually impaired and blind graduates from a higher educational institute in the Maldives. The study employs a narrative inquiry to explore how individuals make sense of their experiences through storytelling, adopting an epistemological stance. This study employs Vygotsky’s sociocultural theory, the emancipatory research paradigm, and Mike Oliver’s social disability model as theoretical frameworks to contextualise the stories while also utilising the emancipatory paradigm to amplify the voices of marginalised groups and empower them. Data is gathered from the purposefully selected nine Maldivian visually impaired graduates from a higher educational institute through in-depth, semi-structured interviews. Labov’s narrative analytics model is used to analyse the data and identify story themes. Ethical considerations are rigorously followed throughout the study, including informed consent, trusting the participants to tell truthful stories, confidentiality, integrity, sensitivity, and relationships with them. This methodological approach helps us understand the participants’ problems and the effects of social interaction, societal support, and attitudes toward visually impaired and blind students. Knowing these makes it easier to create better policies.